Tennis injuries and strategies for prevention. Gender differences in the American junior elite tennis player - Safran, M. R. (2000)
This study compares the incidence and prevalence of injury, and injury patterns in all 14 to 16-year-old participants at the USTA Girls' 16's National Tennis Championships and USTA Boys` National Hardcourt Championships between 1996 and 1999. The results from the first four years of the study are presented here. A tennis profile questionnaire was administered to all participants at the beginning of the tournaments. This questionnaire was then used to compare training and equipment factors in those who sustained injuries during the tournament with those that did not. Over the 4 years studied, there were 741 participants at the Girls' Nationals, with 1,375 singles matches and 328 doubles matches accounting for 4059 athletic exposures. There were 960 participants at the Boys' Nationals, with 1,208 singles matches and 504 doubles matches accounting for 4,432 athletic exposures. During the study period 131 girls (18%) sustained 141 new or recurrent injuries (prevalence rate of 19.0 per 100 athletes) and 160 boys (17%) sustained 177 new or recurrent musculo-skeletal injuries (prevalence rate of 18.4 per 100 athletes) that required evaluation by the medical team during the event. Boys sustained more new injuries during the USTA National Hardcourt Championships as compared with girls. However, there was no significant difference between boys and girls in the overall rate of injury (new and recurrent). Boys and girls have a similar rate of lower extremity injury, both in incidence and prevalence, but the amount of lower extremity injuries was disproportionately greater in girls as compared with boys. Central injuries were significantly fewer in females as compared with males, though the rate of back injury was similar. Both boys and girls have a high rate of injury to the back and shoulder as well as thigh and ankle. Females have more injury to the feet and the leg/calf, while males sustain relatively more injuries to the elbow, hip and knee. Girls had more wrist injuries, which is felt to be due to less upper extremity strength and by being at the end of the kinetic chain. For both boys and girls, strains predominate, followed by inflammation, then sprains. The majority of injuries in boys and girls are chronic, overuse type injuries. For males, 17% were serve and volley players as compared with 3% of females. This may account for the higher incidence of shoulder, back and acute thigh (hamstring and quadriceps strains) injuries in males. With more females playing baseline and all court style, there are longer points, more rallies and the potential for overuse lower extremity injuries and blister type injuries to the feet, as well as overuse injury to the shoulder and back. Much of the problem seems to stem from over-training and overuse. Injured players, male and female, are more likely to train / play longer per year, weight lift, run (and run longer), and do footwork. Many of them have had a significant injury in the previous year, either playing with an injury and trying to compensate for it and/or not fully recovering and/or rehabilitating the previous injury. Either way, the kinetic chain is affected. Overuse or altered mechanics due to the disruption along the kinetic chain probably puts the tennis player at increased risk of injury to the same location, or a different location further along the chain. Protection against skin injury is more prevalent among females, though both males and females neglect eye protection. Back and shoulder injury is most prevalent in elite junior tennis players, as it is in professionals. Further research is necessary to identify potential reasons for these gender-associated variations in injury patterns. With future study, recommendations for injury prevention through improved training and play techniques may be possible to improve tennis performance while reducing the risk of injury.